High resolution DNA barcode library for European butterflies reveals continental patterns of mitochondrial genetic diversity - Vlad Dincă (Nature Portfolio, 2021)
Vlad Dincă, Leonardo Dapporto, and colleagues provide a continental-scale DNA barcode library for 97% of the 473 European butterfly species and examine patterns of haplotype diversity. Results of mitochondrial diversity show elevated haplotype richness in southern European refugia, and this dataset provides a valuable resource for specimen identification, conservation, and research.